The Effect of Mindfulness Therapy on Generalized Anxiety Disorder (GAD) Patients with Anxiety Disorders at Telaga Health Center - Rifki Arrohim Uno; Rona Febriyona Mansur; Nur Uyuun I. Biahimo (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
The high number of anxiety cases, especially Generalized Anxiety Disorder (GAD), in the Telaga Health Center's work area shows that anxiety is still a mental health problem that requires effective intervention in primary health services. One of the non-pharmacological efforts that can be applied is mindfulness therapy. This study aims to determine the effect of mindfulness therapy as an independent variable on the anxiety level of GAD patients as a dependent variable at the Telaga Health Center. This study uses a quasi experiment design with a pretest–posttest control group design. A total of 30 respondents were selected using purposive sampling techniques and divided into intervention groups and control groups. The independent variable was in the form of the administration of mindfulness therapy, while the dependent variable was the anxiety level of GAD patients measured using the GAD-7 questionnaire. Data analysis was carried out by the Wilcoxon Signed Rank Test. The results showed that the administration of mindfulness therapy had a significant effect on reducing anxiety levels in the intervention group (p<0.05), while the control group showed no significant change (p>0.05). It was concluded that mindfulness therapy was shown to be effective in lowering the anxiety level of GAD patients. This intervention has the potential to be applied as a safe, simple, and applicable non-pharmacological alternative in primary health services, especially in health centers.